Interface influence on the diffusion mechanisms during the hetero‐epitaxial growth of Aluminum on Ni(100) substrate by molecular dynamics - A. Hassani; H. El Azrak; F. Ediaai; M. Dardouri; K. Sbiaai; A. Hasnaoui; K. Iskafi; A. Tabyaoui; A. Makan (Journal of Applied Surfaces and Interfaces, 2017)
We investigate the mechanism that occurs during aluminum thin film growth on Ni(100) substrate by molecular dynamics simulation and Embedded Atom Method interaction potential. The simulation is performed at 300K using an incident energy of 1eV. The growth of rectangular structure in first layer favoured flattening mechanism for the impact of deposited atoms, and influences the same structure at the beginning of the second and third layers growth by allowing several exchange mechanisms in order to have 2D growth. Beyond fourth layer, rectangular structure becomes absent at the expense on triangular structure formation, favouring the mechanism of simple jumps in presence of high energy barrier of interlayer and disadvantages exchange mechanism, to transform the growth mode into island mode.